Implikasi Hukum Perkembangan Teknologi Dirgantara Terhadap Rezim Hukum Udara Dan Hukum Angkasa - Miriam Mahalia; Rafa Ardhian; Dava Fransisco; Rahmat Rizziawan (GLOBAL SCIENTS PUBLISHER, 2026)
The development of aerospace technology has advanced rapidly over the past decades, resulting in significant changes in the utilization of airspace and outer space. These advancements include innovations such as unmanned aerial vehicles, communication satellites, and flight technologies capable of operating in the boundary area between the atmosphere and outer space. Nevertheless, these technological developments give rise to complex legal challenges due to fundamental differences between the air law regime, which recognizes full state sovereignty over national airspace, and the space law regime, which is based on the principles of freedom and the prohibition of national appropriation. This study employs a normative legal research method using statutory and conceptual approaches to examine the legal implications of aerospace technological developments on both legal regimes. The findings indicate that the rapid advancement of aerospace technology requires the harmonization and adaptation of existing legal frameworks to ensure their continued relevance in protecting state sovereignty and national interests in the modern era.